2020
DOI: 10.1038/s41537-020-00124-1
|View full text |Cite
|
Sign up to set email alerts
|

Self-perceived cognitive impairments in psychosis ultra-high risk individuals: associations with objective cognitive deficits and functioning

Abstract: There is a scarcity of evidence on subjectively reported cognitive difficulties in individuals at ultra-high risk (UHR) for psychosis and whether these self-perceived cognitive difficulties may relate to objective cognitive deficits, psychopathology, functioning, and adherence to cognitive remediation (CR). Secondary, exploratory analyses to a randomized, clinical trial were conducted with 52 UHR individuals receiving a CR intervention. Participants completed the Measure of Insight into Cognition—Self Report (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…Subjective measures, on the other hand, are better at capturing complex everyday situations, but are more easily influenced by confounding emotional states [88]. Since the discrepancy between subjective and objective measures of cognition is often larger among persons with schizophrenia than in healthy samples, caution should be exercised in the interpretation of the mechanisms of change in subjective EF in the present study [89][90][91][92]. That is not to say that self-reported executive functioning is not of clinical importance as it has been shown to predict important life outcomes, for example academic performance in college [93], and impulse control in younger people [94].…”
Section: Discussionmentioning
confidence: 99%
“…Subjective measures, on the other hand, are better at capturing complex everyday situations, but are more easily influenced by confounding emotional states [88]. Since the discrepancy between subjective and objective measures of cognition is often larger among persons with schizophrenia than in healthy samples, caution should be exercised in the interpretation of the mechanisms of change in subjective EF in the present study [89][90][91][92]. That is not to say that self-reported executive functioning is not of clinical importance as it has been shown to predict important life outcomes, for example academic performance in college [93], and impulse control in younger people [94].…”
Section: Discussionmentioning
confidence: 99%
“…The CANTAB [239] offers a selection of cognitive tests, representing the core neurocognitive domains, and has proven sensitive to cognitive deficits in patients with a FEP [223] and UHR individuals [240,241]. Hence, the CANTAB tests Finally, the Measure of Insight into Cognition-Self Report (MIC-SR) represents a measure of self-perceived cognitive ability that has been recently found to be related with overall functioning and QoL in UHR individuals [242].…”
Section: Assessment Of Neurocognitive Deficitsmentioning
confidence: 99%
“…Finally, the Measure of Insight into Cognition-Self Report (MIC-SR) represents a measure of self-perceived cognitive ability that has been recently found to be related with overall functioning and QoL in UHR individuals [ 242 ].…”
Section: Assessment Of Cognitive Impairment In Early Intervention Set...mentioning
confidence: 99%
“…A substantial portion of people with schizophrenia report fewer subjective cognitive complaints relative to their objectively measured difficulties ( Harvey and Pinkham, 2015 ; Haugen et al, 2021 ; Potvin et al, 2014 ). Individuals with psychosis risk syndromes, on the other hand, are more likely to report greater subjective complaints compared to objective test performance ( Glenthøj et al, 2020 ). Discrepancy in either direction could be an obstacle for GMT.…”
Section: Introductionmentioning
confidence: 99%
“…In two other remediation trials subjective complaints was not a prerequisite for gains in objective cognition, but was associated with better attendance ( Burton and Twamley, 2015 ; Saperstein et al, 2020 ). A study in psychosis risk found that subjective cognition did not moderate outcome ( Glenthøj et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%